Beyond Human Touch Perception: An Adaptive Robotic Skin Based on Gallium Microgranules for Pressure Sensory Augmentation. Issue 44 (3rd October 2022) - Lee, Simok; Byun, Sang‐Hyuk; Kim, Choong Yeon; Cho, Sungwoo; Park, Steve; Sim, Joo Yong; Jeong, Jae‐Woong
Abstract : Robotic skin with human‐skin‐like sensing ability holds immense potential in various fields such as robotics, prosthetics, healthcare, and industries. To catch up with human skin, numerous studies are underway on pressure sensors integrated on robotic skin to improve the sensitivity and detection range. However, due to the trade‐off between them, existing pressure sensors have achieved only a single aspect, either high sensitivity or wide bandwidth. Here, an adaptive robotic skin is proposed that has both high sensitivity and broad bandwidth with an augmented pressure sensing ability beyond the human skin. A key for the adaptive robotic skin is a tunable pressure sensor built with uniform gallium microgranules embedded in an elastomer, which provides large tuning of the sensitivity and the bandwidth, excellent sensor‐to‐sensor uniformity, and high reliability. Through the mode conversion based on the solid–liquid phase transition of gallium microgranules, the sensor provides 97% higher sensitivity (16.97 kPa −1 ) in the soft mode and 262.5% wider bandwidth (≈1.45 MPa) in the rigid mode compared to the human skin. Successful demonstration of the adaptive robotic skin verifies its capabilities in sensing a wide spectrum of pressures ranging from subtle blood pulsation to body weight, suggesting broad use for various applications. Abstract : S. Lee, S.‐H. Byun, C. Y. Kim, S. Cho, S. Park, J. Y. Sim, J.‐W. Jeong An adaptive robotic skin with augmented pressure sensing ability is introduced. Integrated tunable pressure sensors built with uniform gallium microgranules provide high sensitivity and bandwidth and excellent sensor‐to‐sensor uniformity, enabling a large‐scale robotic skin with sensing performance superior to human skin. Proof‐of‐concept demonstrations show its unique sensing capability and versatility covering a broad range of pressure.